UTILIZATION OF BABY-FRIENDLY SERVICES IN MATERNITY WARDS IN SERBIA - Živković Šulović, Mirjana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction/aim: Breastfeeding, as a topic for health promotion and research, continues to be relevant due to numerous benefits for both the child (decreased mortality, strengthening of immunity, reduction of allergies, respiratory and digestive disorders, obesity and diabetes, increased IQ) and the mother (reduced risk of hypertension, diabetes, hyperlipidemia, cardiovascular diseases, breast and ovarian cancer). The study aims to propose effective and efficient health promotion activities directed towards increasing the percentage of exclusively breastfed newborns and infants up to six months of age, in Serbia. Method: The study was conducted as a secondary analysis of data obtained in Multiple Indicator Cluster Survey 6 (MICS 6) for the national and the Roma ethnic group sample, in Serbia, in 2019. The association between the utilization of the following services: skin-to-skin contact, early breastfeeding, and full-time rooming-in for mother and baby, and the socio-demographic variables of mothers, were examined using univariate and multivariate logistic regression analysis. Statistical significance was determined at p < 0.05 (Student t-test, Pearson’s chi-square test, and Mann-Whitney U-test). Results: The examined socio-economic characteristics of the mothers in both samples were not associated with the use of baby-friendly services. A significant statistical difference exists in relation to the type of delivery in both samples. Women who gave birth by caesarean section remain deprived of utilizing the procedures that have proven positive short-term and long-term effects on the health of both the child and mother. In both samples, there was a significant increase in rooming-in in the Belgrade region, where the maternity hospital leading the National Breastfeeding Support Program is located. Conclusion: The most effective measures to improve breastfeeding are related to the adoption of breastfeeding support policies in health facilities and the obligation to train the entire staff who are in contact with mothers during their stay at the maternity hospital (20-hour WHO breastfeeding counseling training).